IMPROVING DESCRIPTIVE WRITING SKILLS USING THE DRILL METHOD AMONG STUDENTS CLASS VII-2 AT PANGERAN ANTASARI JUNIOR HIGH SCHOOL IN MEDAN - Dessi Tanjung; Qurrata A'yunin; Maya Safhida (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to improve the ability to write descriptive essays using the drill method among seventh-grade students in Class VII-2 at Pangeran Antasari Junior High School in Medan. The use of the drill method is expected to help students understand the material and write descriptive essays, thereby improving their skills. This study was conducted at Pangeran Antasari Junior High School in Medan. The research subjects were the 7th-grade Class 2, consisting of 30 students. The study was conducted in two cycles, with each cycle consisting of two sessions. Research data were obtained from (1) observations, (2) interviews, and (3) tests in the form of student assignments (written work) and photographic documentation taken during the activities. The results of the study indicate that the use of the drill method can improve students’ ability to write descriptive essays. This is evidenced by improvements in the learning process, particularly in the learning environment, where students are more focused during instruction. This is evident in the pre-cycle average student score of 66.16; in Cycle I, the average score increased to 73.5, and in Cycle II, it further increased to 82.5. Overall, in Cycle II, all aspects of descriptive writing showed a highly significant improvement. Based on these research results, it can be concluded that the use of the drill method was successful and capable of improving the descriptive writing skills of seventh-grade students in Class VII-2 at Pangeran Antasari Junior High School in Medan.